Depiction of digital literacy practices by English language education lecturers in EFL classrooms - Rahmadani, Mutia (Universitas Jambi, Indonesia, 2024)
This present research explores the digital literacy practices of lecturers in the English Language Education Department at Universitas Negeri Yogyakarta. It comprises lecturers’ perspectives and experiences to provide a vivid overview of digital literacy in EFL classrooms, particularly in higher education contexts. Through descriptive qualitative methods, the data were gathered from eight experienced English lecturers at Universitas Negeri Yogyakarta using snowball or chain sampling. The data were collected through semi-structured interviews, in-class observation, and a collection of learning artifacts. This research revealed that digital literacy was being incorporated within many English courses offered in the English department and several study programs at Universitas Negeri Yogyakarta. Unfortunately, the incorporation of digital literacy has only scratched the surface. Digital literacy practices were still limited to their application in classroom settings without effectively including a proper scheme on how it was incorporated and assessed. Thus, this research becomes ‘eye-opening’ for educators to leverage digital literacy in their teaching for forthcoming appropriateness.